2008
DOI: 10.21897/rta.v13i2.670
|View full text |Cite
|
Sign up to set email alerts
|

Cuantificación de Sustancias Marcadoras de Envejecimiento en Quercus humboldtii por Cromatografía Líquida de Alta Eficiencia

Abstract: En la etapa de maduración de las bebidas alcohólicas se utilizan barriles de roble Americanos y Franceses, que al contacto con el aguardiente liberan sustancias que finalmente contribuyen con las características sensoriales del mismo. El siringaldehido y la vainillina son algunos de estos compuestos que a su vez son considerados como marcadores de envejecimiento ya que son útiles para evaluar la calidad de las bebidas envejecidas. El objetivo de este trabajo fue investigar por primera vez en Colombia l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…The phenolic composition (ellagitannins and low molecular weight phenols) of green Q. humboldtii was characterized and compared to traditional oak wood species, with the most abundant phenolic acids, aldehydes, and ellagitannins being the same as in Q. alba and Q. petraea, and with a phenolic composition closer to that of the American ones [16]. The study on syringaldehyde and vanillin contents showed a similar vanillin concentration to Q. Faginea in toasted wood and a balanced syringaldehyde/vanillin relationship, a marker usually used to characterize oak wood quality [88], when seasoned and toasted. Q. humbolditti had comparable low molecular weight phenols to woods of Q. petraea and Q. alba.…”
Section: Quercus Humboldtii Bonplmentioning
confidence: 97%
See 1 more Smart Citation
“…The phenolic composition (ellagitannins and low molecular weight phenols) of green Q. humboldtii was characterized and compared to traditional oak wood species, with the most abundant phenolic acids, aldehydes, and ellagitannins being the same as in Q. alba and Q. petraea, and with a phenolic composition closer to that of the American ones [16]. The study on syringaldehyde and vanillin contents showed a similar vanillin concentration to Q. Faginea in toasted wood and a balanced syringaldehyde/vanillin relationship, a marker usually used to characterize oak wood quality [88], when seasoned and toasted. Q. humbolditti had comparable low molecular weight phenols to woods of Q. petraea and Q. alba.…”
Section: Quercus Humboldtii Bonplmentioning
confidence: 97%
“…Cooperage products made from this "White oak" have normally been used to age alcoholic beverages, such as rum [87] or brandy. Recently, three studies on the composition of this oak when green and before and after toasting have been published [16,17,88]. The phenolic composition (ellagitannins and low molecular weight phenols) of green Q. humboldtii was characterized and compared to traditional oak wood species, with the most abundant phenolic acids, aldehydes, and ellagitannins being the same as in Q. alba and Q. petraea, and with a phenolic composition closer to that of the American ones [16].…”
Section: Quercus Humboldtii Bonplmentioning
confidence: 99%
“…El Instituto Internacional para la Educación Superior en América Latina y el Caribe en adelante IESALC (2006) y González (2008) consideran que generalmente la repitencia escolar está asociada a la eficiencia del sistema educativo. La eficiencia de una política educativa se refleja en la capacidad de cumplir con tareas optimizando los recursos.…”
Section: Causas De La Repitencia Escolarunclassified
“…Los trabajos investigativos de González (2008) y MEN (2003, concluyen que la repitencia escolar obedece a condiciones socioeconómicas del estudiante. Incluso van más allá y establecen que la repitencia es recurrente en establecimientos educativos ubicados en contextos con niveles socioeconómicos bajos.…”
Section: Causas De La Repitencia Escolarunclassified